Speckle Imaging with an Electron-multiplying CCD Camera at the WIYN Telescope - Horch, Elliott; Anderson, L.; DeSousa, M.; van Altena, W. F. (Bulletin of the American Astronomical Society, 2009)
Electron-multiplying CCD (EMCCD) cameras have extremely strong characteristics for speckle imaging including high quantum efficiency, extremely low effective read noise, and high bandwidth. We report on our first results for binary star astrometry and photometry using an Andor iXon EMCCD at the WIYN 3.5-m Telescope at Kitt Peak. We find that diffraction-limited image reconstructions can be achieved to approximately 15th magnitude and that the device appears to deliver reliable differential photometry of the components of binary star systems. Some implications for stellar astrophysics are discussed.
Conference Name: AAS/Division of Dynamical Astronomy Meeting #40 ADS Bibcode: 2009DDA....40.1604H
Keywords: ⛔ No DOI found

Understanding Physics - Cummings, Karen (Wiley, 2004)
Keywords: Physics; dept.phy; faculty_collection

Understanding Physics: Students Solutions Manual - Cummings, Karen (Wiley, 2004)
Keywords: Physics; Physics; Problems; exercises; etc; dept.phy; faculty_collection

Improving 4H-SiC/SiO2 interface properties by depositing ultra-thin Si nitride layer prior to formation of SiO2 and annealing - Wang, X.W.; Bu, H.M.; Laube, B.L.; Caragianis-Broadbridge, C.; Ma, T.P. (Mater. Sci. Forum, 2002)
We report dramatic improvement in electrical properties of 4H-SiC/SiO2 interface by depositing an ultra-thin layer of silicon nitride on 4H-SiC prior to formation of silicon oxide and annealing. AC conductance measurements reveal interface-trap density equal to or below 1 × 1012/cm2- eV at energies near the conduction band edge. XPS spectra confirm the presence of N at the interface and suggest possible bonding between N and C. © (2002) Trans Tech Publications, Switzerland.
1 citations (Crossref) [2023-10-31] Journal Abbreviation: Mater. Sci. Forum
Keywords: 4H-SiC MOS; Angle-resolved; Angle-resolved x-ray; Annealing; Chemical bonds; Conductance measurement; Conduction band edge; Deposition; Gate dielectrics; Interface trap density; Interfaces (materials); MOS devices; Nitride layers; Nitrides; Photoelectron spectroscopy; Photoelectron spectroscopy (ARXPS); Si-CMOS; SiC/siO2-interfaces; Silica; Silicon carbide; Silicon nitride; Silicon oxides; Ultrathin films; Ultrathin layers; X ray photoelectron spectroscopy; dept.phy

Theory of paramagnetic scattering in highly frustrated magnets with long-range dipole-dipole interactions: The case of the Tb2Ti 2O7 pyrochlore antiferromagnet - Enjalran, M.; Gingras, M.J.P. (Physical Review B - Condensed Matter and Materials Physics, 2004)
Highly frustrated antiferromagnets composed of magnetic rare-earth moments are currently attracting much experimental and theoretical interest. Rare-earth ions generally have small exchange interactions and large magnetic moments. This makes it necessary to understand in detail the role of long-range magnetic dipole-dipole interactions in these systems, in particular, in the context of spin-spin correlations that develop in the paramagnetic phase, but are often unable to condense into a conventional long-range magnetic-ordered phase. This scenario is most dramatically emphasized in the frustrated pyrochlore antiferromagnet material Tb2Ti2O7, which does not order down to 50 mK despite an antiferromagnetic Curie-Weiss temperature TCW∼-20 K. In this paper we report results from mean-field theory calculations of the paramagnetic elastic neutron scattering in highly frustrated magnetic systems with long-range dipole-dipole interactions, focusing on the Tb2Ti2O7 system. Modeling Tb 2Ti2O7 as an antiferromagnetic 〈111〉 Ising pyrochlore, we find that the mean-field paramagnetic scattering is inconsistent with the experimentally observed results. Through simple symmetry arguments we demonstrate that the observed paramagnetic correlations in Tb 2Ti2O7 are precluded from being generated by any spin Hamiltonian that considers only Ising spins, but are qualitatively consistent with Heisenberg-like moments. Explicit calculations of the paramagnetic scattering pattern for both 〈111〉 Ising and Heisenberg models, which include finite single-ion anisotropy, support these claims. We offer suggestions for reconciling the need to restore spin isotropy with the Ising-like structure suggested by the single-ion properties of Tb3+.
74 citations (Crossref) [2023-10-31]
Keywords: anisotropy; antiferromagnets; article; atom; calculation; dept.phy; dipole; magnetism; mathematical analysis; molecular interaction; neutron scattering; oxygen; paramagnetic scattering; temperature; terbium; thallium; theory

Neutron scattering investigation of the spin ice state in Dy 2Ti2O7 - Fennell, T.; Petrenko, O.A.; Fåk, B.; Bramwell, S.T.; Enjalran, M.; Yavors'kii, T.; Gingras, M.J.P.; Melko, R.G.; Balakrishnan, G. (Physical Review B - Condensed Matter and Materials Physics, 2004)
Dy2Ti2O7 has been advanced as an ideal spin ice material. We present a neutron scattering investigation of a single-crystal sample of 162Dy2Ti2O 7. The scattering intensity has been mapped in zero applied field in the h,h,l and h,k,0 planes of reciprocal space at temperatures between 0.05 and 20 K. The measured diffuse scattering has been compared with that predicted by the dipolar spin ice model. The comparison is good, except at the Brillouin-zone boundaries where extra scattering appears in the experimental data. It is concluded that the dipolar spin ice model provides a successful basis for understanding Dy2Ti2O7, but that there are issues which remain to be clarified.
60 citations (Crossref) [2023-10-31]
Keywords: Monte Carlo method; article; crystal; dept.phy; dysprosium; neutron scattering; temperature; temperature dependence; titanium

Electrical properties of mismatched interface between InP and GaP - Li, G.-H.; Sun, Y.-N.; Yulius, A.; Broadbridge, C.C.; Woodall, J.M. (Rengong Jingti Xuebao/Journal of Synthetic Crystals, 2007)
The electrical properties of the mismatched interface between InP and GaP have been investigatedted. High resolution transmission electron microscopy (HRTEM) image shows the presence of strain relieving, 90° misfit dislocations at the InP/GaP interface. Electrochemical capacitance voltage (ECV) profiling indicates the presence of a high-density sheet of carriers at the interface. AFM image shows a pretty good InP epitaxial layer with surface roughness of 2.48 nm has been obtained. A model based on Fermi-level pinning in InP at the interface by misfit dislocations is proposed to account for the observed electrical behavior.
Keywords: Dislocations; InP/GaP interface; Lattice mismatch; dept.phy; ⛔ No DOI found

Normalized change - Marx, J.D.; Cummings, K. (American Journal of Physics, 2007)
Discussions of diagnostic tools that gauge students' conceptual understanding permeate the literature. Many instructors report their class' normalized gain to characterize the change in scores from pre-test to post-test. We describe a new procedure for characterizing these changes. This procedure, which we call the normalized change, c, involves the ratio of the gain to the maximum possible gain or the loss to the maximum possible loss. We also advocate reporting the average of a class' normalized changes and utilizing a particular statistical and graphical approach for comparing average c values. © 2007 American Association of Physics Teachers.
155 citations (Crossref) [2023-10-31]
Keywords: dept.phy

The stellar mass spectrum of the open cluster NGC 3293 - Slawson, R.W.; Ninkov, Z.; Horch, E.P. (Astrophysics and Space Science, 2007)
We have obtained and analyzed UBVRI CCD frames of the young, 4-10 Myr, open cluster NGC 3293 and the surrounding field in order to study its stellar content and determine the cluster's IMF. We found significantly fewer lower mass stars, M≤2.5M ⊙, than expected. This is particularly so if a single age for the cluster of 4.6 Myr is adopted as derived from fitting evolutionary models to the upper main sequence. Some intermediate-mass stars near the main sequence in the HR diagram imply an age for the cluster of about 10 Myr. When compared with the Scalo (The stellar initial mass function. ASP conference series, vol. 24, p. 201, 1998) IMF scaled to the cluster IMF in the intermediate mass range, 2.5≤M/M ⊙≤8.0 where there is good agreement, the high mass stars have a distinctly flatter IMF, indicating an over abundance of these stars, and there is a sharp turnover in the distribution at lower masses. The radial density distribution of cluster stars in the massive and intermediate mass regimes indicate that these stars are more concentrated to the cluster core whereas the lower-mass stars show little concentration. We suggest that this is evidence supporting the formation of massive stars through accretion and/or coagulation processes in denser cluster cores at the expense of the lower mass proto-stars. © 2007 Springer Science+Business Media B.V.
3 citations (Crossref) [2023-10-31]
Keywords: Mass function; Open clusters and associations: individual (NGC 3292); Stars: luminosity function; dept.phy

MOCVD growth and characterization of AlGaInN nanowires and nanostructures - Han, J.; Kim, K.; Su, J.; Gherasimova, M.; Nurmikko, A.V.; Chichibu, S.F.; Broadbridge, C. (Mater Res Soc Symp Proc, 2006)
Growth of GaN and AlGaInN nanowires using metalorganic chemical vapor deposition (MOCVD) is investigated. It is determined that surface kinetics play an important role in non-equilibrium synthesis process such as MOCVD, in contrast to near-equilibrium synthesis by hotwall furnace reactor. Examination of crystallographic properties of GaN nanowires reveals preferential growth directions which are perpendicular to the c-axis. Such a tendency is analyzed by both thermodynamic and kinetic arguments and attributed to the minimization of (side wall) surface energy. Spontaneous formation of Al(Ga)N/GaN coaxial nanowires with distinct emission at 370 nm is observed. It is identified that the interplay between surface kinetics and thermodynamics facilitates the catalytic growth of GaN core while a limited surface diffusion of Al adatoms leads to nonselective, vapor-solid growth of Al(Ga)N sheath. The knowledge of crystallographic alignment is applied to the formation of arrayed GaN nanowires in both vertical and horizontal fashions, resulting in potentially new paradigms for creating nanoscale devices. © 2006 Materials Research Society.
Journal Abbreviation: Mater Res Soc Symp Proc
Keywords: Crystal growth; Crystallography; Diffusion; Growth directions; Interfacial energy; Metallorganic chemical vapor deposition; Nanostructured materials; Nanostructures; Nanotechnology; Nanowires; Semiconductor quantum wires; dept.phy; non equilibrium synthesis

Spin hamiltonian, competing small energy scales, and incommensurate long-range order in the highly frustrated Gd3Ga5O12 garnet antiferromagnet - Yavors'kii, T.; Enjalran, M.; Gingras, M.J.P. (Physical Review Letters, 2006)
Despite the availability of a spin Hamiltonian for the Gd3Ga5O12 garnet (GGG) for over 25 years, there has so far been little theoretical insight regarding the many unusual low temperature properties of GGG. Here we investigate GGG in zero magnetic field using mean-field theory. We reproduce the spin liquid-like correlations and, most importantly, explain the positions of the sharp peaks seen in powder neutron diffraction experiments. We show that it is crucial to treat accurately the long-range nature of the magnetic dipolar interactions to allow for a determination of the small exchange energy scales involved in the selection of the experimental ordering wave vector. Our results show that the incommensurate order in GGG is classical in nature, intrinsic to the microscopic spin Hamiltonian and not caused by weak disorder. © 2006 The American Physical Society.
31 citations (Crossref) [2023-10-31]
Keywords: Antiferromagnetic materials; Electron energy levels; Garnet antiferromagnets; Hamiltonians; Magnetic dipolar interactions; Magnetic fields; Mean field theory; Neutron diffraction; Ordering wave vectors; Quantum theory; dept.phy

A photometric analysis of seventeen binary stars using speckle imaging - Davidson Jr., J.W.; Baptista, B.J.; Horch, E.P.; Franz, O.; Van Altena, W.F. (Astronomical Journal, 2009)
Magnitude differences obtained from speckle imaging are used in combination with other data in the literature to place the components of binary star systems on the H-R diagram. Isochrones are compared with the positions obtained, and a best-fit isochrone is determined for each system, yielding both masses of the components as well as an age range consistent with the system parameters. Seventeen systems are studied, 12 of which were observed with the 0.6 m Lowell-Tololo Telescope at Cerro Tololo Inter-American Observatory and six of which were observed with the WIYN 3.5 m Telescope (The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, Yale University, and the National Optical Astronomy Observatories) at Kitt Peak. One system was observed from both sites. In comparing photometric masses to mass information from orbit determinations, we find that the photometric masses agree very well with the dynamical masses, and are generally more precise. For three systems, no dynamical masses exist at present, and therefore the photometrically determined values are the first mass estimates derived for these components. © 2009 The American Astronomical Society. All rights reserved.
11 citations (Crossref) [2023-10-31]
Keywords: Binaries: visual techniques; High angular resolution techniques; Interferometric techniques; Photometric; dept.phy; peer-reviewed

Binary and multiple stars - Horch, E. (Astrometry for astrophysics: Methods, Models, and Applications, 2009)
Introduction Two or more stars that are located close together in space interact gravitationally, causing deviations from linear motion as each star is accelerated. If we consider the case of two stars with a physical separation of many times the radius of either star (but still close enough to generate significant accelerations), it is sufficient to consider the stars as point masses. The equations of motion for such a system can be solved by assuming the inverse-square law of gravity and applying Newton's laws of motion. Newton's solution elegantly explained Kepler's laws of planetary motion, since one of the general solutions of motion is an ellipse with the more massive body (the Sun, in the case of the Solar System) at one focus. Kepler's third law of planetary motion (i.e. the harmonic law) as applied to the binary-star situation can be written where m1 and m2 are the masses of the two stars in solar units, a is the semi-major axis of the relative orbital ellipse in astronomical units, and P is the orbital period of the system in years. If you can only apply this formula, then it is not possible to obtain individual masses from the observables on the right-hand side, nor is the mass sum possible without an estimate of the parallax of the system (which allows for the conversion of a from an angular measure to astronomical units). Furthermore, while it is usually possible to measure the orbital period to high precision, the application of the formula is complicated by the fact that the semi-major axis, and implicitly the parallax, is raised to the third power. © Cambridge University Press 2013.
Journal Abbreviation: Astrometry for astrophysics: Methods, Models, and Applications
Keywords: dept.phy

Growth of AlGaN nanowires by metalorganic chemical vapor deposition - Su, J.; Gherasimova, M.; Cui, G.; Tsukamoto, Hironori; Han, J.; Onuma, T.; Kurimoto, M.; Chichibu, Shigefusa F.; Broadbridge, Christine; He, Y.; Nurmikko, Arto V. (Applied Physics Letters, 2005)
Growth of ternary AlGaN nanowires using metalorganic chemical vapor deposition is investigated. Structural, chemical, and optical characterization at nanoscopic scale is carried out by high resolution transmission electron microscopy, x-ray energy dispersive spectroscopy, and spatially resolved cathodoluminescence. Spontaneous formation of Al (Ga) NGaN coaxial nanowires with distinct emission at 370 nm is observed. It is identified that the interplay between surface kinetics and thermodynamics facilitates the catalytic growth of GaN core while a limited surface diffusion of Al adatoms leads to nonselective, vapor-solid growth of Al(Ga)N sheath. The observation points to a fundamental difference in nanosynthesis using near-equilibrium and nonequilibrium techniques. © 2005 American Institute of Physics.
37 citations (Crossref) [2023-10-31] Citation Key Alias: pop00071 tex.type: [object Object]
Keywords: Aluminum compounds; Cathodoluminescence; Coaxial nanowires; Energy dispersive spectroscopy; Metallorganic chemical vapor deposition; Nanoscopic scale; Nanostructured materials; Optical properties; Reaction kinetics; Surface kinetics; Synthesis (chemical); Transmission electron microscopy; X-ray energy dispersive spectroscopy; dept.phy

Comparison of extended x-ray absorption fine structure and Scherrer analysis of x-ray diffraction as methods for determining mean sizes of polydisperse nanoparticles - Calvin, Scott; Luo, Shuixiang; Caragianisbroadbridge, C; Mcguinness, J K; Anderson, Eric; Lehman, A; Wee, K H; Morrison, Shannon A; Kurihara, L K (Applied Physics Letters, 2005)
Curve fitting of extended x-ray absorption fine structure (EXAFS) spectra, transmission electron microscopy (TEM) imaging, and Scherrer analysis of x-ray diffraction (XRD) are compared as methods for determining the mean crystallite size in polydisperse samples of platinum nanoparticles. By applying the techniques to mixtures of pure samples, it is found that EXAFS correctly determines the relative mean sizes of these polydisperse samples, while XRD tends to be weighted more toward the largest crystallites in the sample. Results for TEM are not clear cut, due to polycrystallinity and aggregation, but are consistent with the other results. © 2005 American Institute of Physics.
68 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-863-384-595-634 tex.type: [object Object]
Keywords: Curve fitting; Diffraction; EXAFS; Imaging techniques; Nanostructured materials; Platinum; Platinum nanoparticles; Polydisperse samples; Transmission electron microscopy; X ray diffraction; dept.phy

Conceptual Underpinnings of Students’ Ability to Understand Reflections from a Plane Mirror - Cummings, Karen (AIP Conference Proceedings, 2005)
In this paper we explore students' pre-instruction knowledge of several conceptual and procedural pieces of knowledge that we believe are prerequisite to one's ability to generate correct light ray diagrams and understand image formation by a plane mirror. The research population is an algebra-based, introductory physics class of about 50 students at a medium-sized, urban, public university. Both individual interviews and written free response questions were used to gather data. © 2005 American Institute of Physics.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/096-094-774-595-400, pop00418 tex.number: [object Object]
Keywords: dept.phy

An exploration of microscopy for educational applications in the high school classroom - Fitzsimmons, Ryan; Koekkoek, Robert; Caragianis-Broadbridge, Christine; Lehman, Ann; Cummings, Karen (MRS Proceedings, 2005)
This project was initiated with an undergraduate student's exploration of two advanced research tools: the scanning electron microscope (SEM) and the atomic force microscope (AFM). A research project was developed to study the application of microscopy to introductory physics instruction, Nine modules covering various aspects of introductory physics were created. Module components included discussions, laboratory experiments and assessments. Four of the nine modules were implemented in various high school classes. Assessments were used to compare student learning with the modules versus standard textbook/lecture techniques, Preliminary results of this study are presented along with recently developed methods created to facilitate implementation of these modules within the high school classroom. © 2006 Materials Research Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/060-305-083-686-777 tex.type: [object Object]
Keywords: Atomic force microscopy; Education; Project management; Scanning electron microscopy; School buildings; School classroom; Student learning; dept.phy

A preliminary investigation of the efficacy of oral motor exercises for children with mild articulation disorders - Guisti Braislin, M.A.; Cascella, P.W. (International Journal of Rehabilitation Research, 2005)
Although oral motor therapy is sometimes used to treat articulation disorders in school-age children, several reports question its efficacy. In this case study, four first-grade students, two boys and two girls, received 15 half-hour sessions of oral motor treatment based on Easy Does it for Articulation: An Oral Motor Approach (). Pre- and post-test measures of the children's articulation indicated no real differences in speech production. These results question the efficacy of general and discrete oral motor exercises because they did not enhance the children's speech production. © 2005 Lippincott Williams & Wilkins.
19 citations (Crossref) [2023-10-31]
Keywords: *Articulation Disorders/th [Therapy]; *Exercise Therapy/mt [Methods]; *Mouth; Articulation; Articulation Disorders; Articulation disorders; Child; Efficacy; Exercise Therapy; Exercise equipment; Female; Humans; Male; Mouth; Oral motor exercises; Patient monitoring; Patient rehabilitation; Speech; Speech production; Treatment Outcome; article; case report; child; consonant; dept.phy; efficacy; female; human; interrater reliability; kinesiotherapy; male; methodology; mouth; oral motor exercises; preschool child; priority journal; speech articulation; speech disorder; speech therapy; standardization; treatment indication; treatment outcome

Catalytic growth of group III-nitride nanowires and nanostructures by metalorganic chemical vapor deposition - Su, J; Cui, G; Gherasimova, M; Tsukamoto, Hironori; Han, J; Ciuparu, Dragos; Lim, Sangyun; Pfefferle, Lisa D; He, Y; Nurmikko, A V; Broadbridge, Christine; Lehman, Ann Hein (Applied Physics Letters, 2005)
We report flexible synthesis of group III-nitride nanowires and nanostructures by metalorganic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Supersaturation and surface stoichiometry strongly influence the stability of liquid droplets and growth selectivity. To facilitate and sustain the VLS growth, indium catalyst is introduced based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst droplets and to promote nucleation statistics. Both GaN and AlN nanowires have been synthesized using MOCVD. Three-dimensional AlNGaN trunk-branch nanostructures are reported to illustrate the versatility of incorporating the VLS mechanism into MOCVD process. © 2005 American Institute of Physics.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-539-752-343-072 tex.type: [object Object]
Keywords: Catalysis; Catalysts; Growth kinetics; Indium; Metallorganic chemical vapor deposition; Molecular sieves; Nanostructured materials; Nanowires; Nitrides; Nucleation; Scanning electron microscopy; Stoichiometry; Supersaturation; Synthesis (chemical); Thermodynamics; Transmission electron microscopy; Trimethyl-gallium (TMGa); Trimethylaluminum (TMAl); Vapor-solid-liquid (VLS) growth mechanism; dept.phy

A hybrid epitaxy method for InAs on GaP - Chen, A; Yulius, Aristo; Woodall, J M; Broadbridge, Christine (Applied Physics Letters, 2004)
The interface formation mechanism during the molecular-beam epitaxy (MBE) of InAs/GaP has been studied with the aid of the In-Ga-P phase diagram. It is discovered that an initial dissolution and crystallization process similar to liquid phase epitaxy (LPE) may happen at sufficiently high temperature, resulting in a graded composition at the interface. Consequently, "parasitic LPE/MBE" is the name for this hybrid form of MBE. High-resolution TEM images confirm the existence of the interfacial layer in the sample grown at high temperature. The graded interface smears out the band offset and leads to a nonrectifying heterojunction. Low-temperature (LT) MBE growth can turn off the LPE component, enabling the growth of an abrupt interface. Based on this "LPE/MBE" model, a LT MBE technique is developed to grow an abrupt InAs/InGaP interface for heterojunction power Schottky rectifiers. The LT InAs/InGaP heterojunction demonstrates nearly ideal Schottky rectifier characteristics, while the sample grown at high temperature shows resistive ohmic characteristics. The LT InAs/InGaP Schottky diode also demonstrates good stability with respect to anneal temperature, similar to the InAs/GaP heterojunctions. © 2004 American Institute of Physics.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-537-776-623-144 tex.type: [object Object]
Keywords: Baliga figure of merit (BFOM); Current voltage characteristics; Liquid phase epitaxy; Metal-semiconductor (MS) diodes; Molecular beam epitaxy; Phase diagrams; Rapid thermal annealer (RTA); Rapid thermal annealing; Schottkey rectifiers; Schottky barrier diodes; Semiconducting gallium compounds; Semiconducting indium compounds; Transmission electron microscopy; dept.phy

Attitudes Toward Problem Solving as Predictors of Student Success - Cummings, Karen (AIP Conference Proceedings, 2004)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/147-561-918-415-471, pop00071 tex.number: [object Object]
Keywords: dept.phy

Vapor-liquid-solid growth of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition - Su, J; Gherasimova, M; Cui, G; Han, J; Lim, Sangyun; Ciuparu, Dragos; Pfefferle, Lisa D; He, Y; Nurmikko, A V; Broadbridge, Christine; Lehman, Ann Hein; Onuma, T; et al. (MRS Proceedings, 2004)
We report flexible synthesis of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Indium is used as an in-situ catalyst to facilitate and sustain the stability of liquid phase droplet for VLS growth based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst droplets and to promote nucleation statistics. Cathodoluminescence (CL) of GaN nanowires shows near band-edge emission at 370nm, and strong E 2 phonon peak is observed at room temperature in Raman scattering spectra. Both binary GaN and AlN nanowires have been synthesized by MOCVD. Three-dimensional AlN/GaN trunk-branch nanostructures are reported to illustrate the versatility of incorporating the VLS mechanism into MOCVD process. © 2005 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-591-869-918-808 tex.type: [object Object]
Keywords: Catalysis; Heterojunctions; Metallorganic chemical vapor deposition; Molecular beam epitaxy; Nanoelectronics; Nanostructured materials; Nanowires; Nucleation; Optical characterization; Synthesis (chemical); Thermodynamics; Vapor-liquid-solid (VLS) growth; dept.phy

Understanding paramagnetic spin correlations in the spin-liquid pyrochlore Tb 2 Ti 2 O 7 - Kao, Ying-Jer; Enjalran, Matthew; Maestro, Adrian Del; Molavian, Hamid R.; Gingras, Michel J. P. (Physical Review B, 2003)
Recent elastic and inelastic neutron scattering studies of the highly frustrated pyrochlore antiferromagnet Tb2Ti2O7 have shown some very intriguing features that cannot be modeled by the local 〈111〉 classical Ising model, naively expected to describe this system at low temperatures. By including single-ion excitations from the ground state doublet to higher crystal field levels, we successfully describe the elastic neutron scattering pattern and dispersion relations in Tb2Ti2O7, quantitatively consistent with experimental observations. © 2003 The American Physical Society.
72 citations (Crossref) [2023-10-31] Citation Key Alias: pop00050 tex.type: [object Object]
Keywords: article; complex formation; correlation analysis; dept.phy; low temperature; molecular model; neutron scattering; oxygen; quantitative analysis; terbium; titanium

Thin film thickness and grain structure determination of ferroelectric SrBi2Ta2O9 with cross-sectional atomic force microscopy - Pechkis, Daniel L.; Caragianis-Broadbridge, Christine; Lehman, Ann Hein; Klein, Kate; Han, Jin-ping; Ma, Tso-Ping (Microscopy and Microanalysis, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00148 tex.type: [object Object]
Keywords: dept.phy

Alloy formation in nanostructured silicon - Gao, Bo; Sinha, Saion K.; Fleming, Les; Zhou, Otto (Advanced Materials, 2001)
250 citations (Crossref) [2023-10-31] Citation Key Alias: pop00001 tex.type: [object Object]
Keywords: dept.phy

Microstructure and physical properties of ferroelectric-gate memory capacitors with various buffer layers - Caragianis-Broadbridge, Christine; Han, J; Ma, T P; Lehman, Ann Hein; Zhu, Wenjuan; Luo, Zhijiong; Pechkis, Daniel; Laube, Bruce L (MRS Proceedings, 2001)
This paper reports the microstructure and physical properties of ferroelectric capacitors formed from SrBi2Ta2O9 (SBT) layers on Si with various buffer layers including jet-vapor deposited silicon nitride, zirconium oxide, hafnium oxide and thermally grown silicon oxide. Results from cross-sectional transmission electron microscopy (X-TEM), energy dispersive spectroscopy (EDS), X-Ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and non-contact atomic force microscopy (nc-AFM) data coupled with capacitance-voltage (C-V) and current-voltage (I-V) data indicate that both the microstructure and physical properties of SBT films deposited on silicon are dependent on the buffer layer material employed.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-822-098-712-167 tex.type: [object Object]
Keywords: Atomic force microscopy; Buffer layers; Capacitance; Capacitors; Electric currents; Electric potential; Energy dispersive spectroscopy; Ferroelectric devices; Ferroelectric-gate memory capacitors; Gates (transistor); Microstructure; Silica; Silicon nitride; Thin films; Transmission electron microscopy; X ray diffraction analysis; X ray photoelectron spectroscopy; dept.phy

Synthesis of silicon nano-dendrites - Sinha, Saion K; Gao, Bo; Zhou, Otto (MRS Proceedings, 2001)
A new branched silicon nanostructure called Silicon Nano-Dendrite (SiND) was prepared by Laser ablation. During the Laser ablation process, the Argon flow was switched on and off very fast and simultaneously decreasing the flow rate, to create a non-steady-state flow. The resulting structure will open up new avenues in molecular electronics as the FeSi2 nano-particle at the end can be used to grow nanotube-nanowire junctions.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-722-833-203-829 tex.type: [object Object]
Keywords: Carbon nanotubes; Electron diffraction; Fullerenes; Laser ablation; Molecular electronic applications; Nanostructured materials; Semiconducting silicon; Semiconductor quantum dots; Silicon nano-dendrites; Synthesis (chemical); Transmission electron microscopy; dept.phy

Ccd speckle observations of binary stars with the wiyn telescope. vi. measures during 2007-2008 - Horch, Elliott P.; Falta, David; Anderson, Lisa M.; DeSousa, Michael D.; Miniter, Craig M.; Ahmed, Tasmia; van Altena, William F. (The Astronomical Journal, 2009)
Results of 974 speckle observations of 546 binary stars are presented. Observations were obtained at the WIYN 3.5 m Telescope at Kitt Peak National Observatory during the time interval from 2007 January to 2008 June. In all cases, the relative separation and position angle of the components are measured, and the magnitude difference is determined in 809 cases. The precision of the results as judged from repeat observations and objects with very well-determined orbits is similar to previous papers in this series, namely ∼ 3 mas in separation and <1° in position angle in most cases. Similarly, the photometric precision remains consistent with previous WIYN speckle data, on average ∼ 0.1 mag per observation. Six systems of special interest are discussed. © 2010. The American Astronomical Society. All rights reserved.
58 citations (Crossref) [2023-10-31] Citation Key Alias: pop00066 tex.type: [object Object]
Keywords: Binaries: visual; Techniques: high angular resolution; Techniques: interferometric; Techniques:Photometric; dept.phy; peer-reviewed

Low loss EELS study of the ultrathin SrTiO3 film grown on the si single crystal - Su, Dong; Couillard, Martin; Sawicki, M; Broadbridge, Christine; Zhu, Y. (Microscopy and Microanalysis, 2009)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00259 tex.type: [object Object]
Keywords: dept.phy

Comparing the force and motion conceptual evaluation and the force concept inventory - Thornton, Ronald K.; Kuhl, Dennis; Cummings, Karen; Marx, Jeffrey (Physical Review Special Topics-Physics Education Research, 2009)
In this paper we compare and contrast student's pretest/post-test performance on the Halloun-Hestenes force concept inventory (FCI) to the Thornton-Sokoloff force and motion conceptual evaluation (FMCE). Both tests are multiple-choice assessment instruments whose results are used to characterize how well a first term, introductory physics course promotes conceptual understanding. However, the two exams have slightly different content domains, as well as different representational formats; hence, one exam or the other might better fit the interests of a given instructor or researcher. To begin the comparison, we outline how to determine a single-number score for the FMCE and present ranges of normalized gains on this exam. We then compare scores on the FCI and the FMCE for approximately 2000 students enrolled in the Studio Physics course at Rensselaer Polytechnic Institute over a period of eight years (1998-2006) that encompassed significant evolution of the course and many different instructors. We found that the mean score on the FCI is significantly higher than the mean score on the FMCE, however there is a very strong relationship between scores on the two exams. The slope of a best fit line drawn through FCI versus FMCE data is approximately 0.54, and the correlation coefficient is approximately r=0.78, for preinstructional and postinstructional testings combined. In spite of this strong relationship, the assessments measure different normalized gains under identical circumstances. Additionally, students who scored well on one exam did not necessarily score well on the other. We use this discrepancy to uncover some subtle, but important, differences between the exams. We also present ranges of normalized gains for the FMCE in a variety of instructional settings.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-428-484-414-954 tex.article-number: [object Object] tex.unique-id: [object Object]
Keywords: dept.phy

Observations of binary stars with the differential speckle survey instrument. i. instrument description and first results - Horch, Elliott P.; Veillette, Daniel R.; Gallé, Roberto Baena; Shah, Sagar C.; O'Rielly, Grant; van Altena, William F. (The Astronomical Journal, 2009)
First results of a new speckle imaging system, the Differential Speckle Survey Instrument, are reported. The instrument is designed to take speckle data in two filters simultaneously with two independent CCD imagers. This feature results in three advantages over other speckle cameras: (1) twice as many frames can be obtained in the same observation time which can increase the signal-to-noise ratio for astrometric measurements, (2) component colors can be derived from a single observation, and (3) the two colors give substantial leverage over atmospheric dispersion, allowing for subdiffraction-limited separations to be measured reliably. Fifty-four observations are reported from the first use of the instrument at the Wisconsin-Indiana-Yale-NOAO 3.5 m Telescope9The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, Yale University, and the National Optical Astronomy Observatories. in 2008 September, including seven components resolved for the first time. These observations are used to judge the basic capabilities of the instrument. © 2009. The American Astronomical Society. All rights reserved.
99 citations (Crossref) [2023-10-31] Citation Key Alias: pop00033 tex.type: [object Object]
Keywords: astrometry; binaries: close; binaries: visual; dept.phy; instrumentation: high angular resolution; instrumentation: interferometers; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Research grade instrumentation for nanotechnology and MSE education - Broadbridge, Christine; Garofano, Jacquelynn; Altman, Eric I; Khalil, Yehia F; Henrich, Victor E; Segal, Y; Padmore, Myrtlerose; Michael, Philip; Walker, Fred (MRS Proceedings, 2009)
The Center for Research on Interface Structures and Phenomena (CRISP) is a National Science Foundation (NSF) Materials Research Science and Engineering Center (MRSEC). CRISP is a partnership between Yale University, Southern Connecticut State University (SCSU) and Brookhaven National Laboratory. A main focus of CRISP research is complex oxide interfaces that are prepared using epitaxial techniques, including molecular beam epitaxy (MBE). Complex oxides exhibit a wealth of electronic, magnetic and chemical behaviors, and the surfaces and interfaces of complex oxides can have properties that differ substantially from those of the corresponding bulk materials. CRISP employs this research program in a concerted way to educate students at all levels. CRISP has constructed a robust MBE apparatus specifically designed for safe and productive use by undergraduates. Students can grow their own samples and then characterize them with facilities at both Yale and SCSU, providing a complete research and educational experience. This paper will focus on the implementation of the CRISP Teaching MBE facility and its use in the study of the synthesis and properties of the crystalline oxide-silicon interface. C 2010 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-591-860-685-232 tex.type: [object Object]
Keywords: Brookhaven national laboratory; Bulk materials; Chemical behavior; Complex oxides; Crystal growth; Crystalline materials; Crystalline oxides; Educational experiences; Epitaxial techniques; Interface structures; Materials research; Materials research societies; Materials science; Molecular beam epitaxy; Molecular beams; National Science Foundations; Research; Research programs; Science and engineering; Silicon interface; Students; Surfaces and interfaces; Yale University; dept.phy

Authentic science research and the utilization of nanoscience in the non-traditional classroom setting - Day, Deborah A; Yu, Zizi; Wang, Zelun; Dalecki, Jennifer; Jadbabaie, Arian; Feng, Emily Z; Mattessich, Thomas J; Caragianis-Broadbridge, Christine; Reed, Mark A; Munden, Ryan (MRS Proceedings, 2009)
Applications of nanoscience in the non-traditional classroom have successfully exposed students to various methods of research with applications to micro- and nano-electronics. Activities obtained from the NanoSense website associated with current global energy and water concerns are solid examples 1. In this regard, all 36 students in the 2008-2009 Science Research Program (SRP) prepared and delivered individual and group lesson plans in addition to their authentic, year-long research projects. Two out of 36 students selected nanoscience based projects in preparation for science fair competition in 2009. Additionally, preliminary research was conducted while participating in the Center for Research on Interface Structures and Phenomena (CRISP) Research Experience for Teachers (RET) Program in summer 2008 which supported the idea of developing a photolithography kit. This kit is intended to introduce high school students to the fundamentals of photolithography. In this paper, the design, implementation and feasibility of this kit in the high school classroom is described as well as details involving individual and group nanoscience based projects. Supporting educational models include self-regulated learning (SRL) concepts: situated cognition; social constructivism; Renzulli's (1977) enrichment triad and Types I - III inquiry enrichment activities 2,3. © 2009 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-237-245-323-128 tex.type: [object Object]
Keywords: Classroom settings; Education computing; Educational models; Global energy; High school; High school students; Interface structures; Lesson plans; Micro- and nano-electronics; Nanoscience; Non-traditional; Photolithography; Research; Research experience; School buildings; Science fairs; Science research; Self-regulated learning; Situated cognition; Social constructivism; Students; Teaching; dept.phy

A Study of Peer Instruction Methods with High School Physics Students - Cummings, Karen; Roberts, Stephen G. (AIP conference proceedings, 2008)
This paper reports on the results of an experiment to test the use of a Peer Instruction (PI) pedagogical model in a small class, high school environment. The study reports findings based on a population of 213 high school students attending algebra based physics courses, both Honors and A level, taught by 5 different instructors. The results show a correlation between use of Peer Instruction and improved student conceptual understanding, as demonstrated by gains on a pre-/post- assessment instrument (FCI). However, there also appears to be a number of other factors that strongly influence the resulting gains. In addition to instructor differences, the data seem to indicate that students who are more "physics-inclined" and can answer questions correctly prior to instruction and prior to any Peer Instruction discussion subsequently achieve higher gains as measured by the FCI. While this is to be expected, the use of normalized gains is intended to mitigate this result, but it appears to be prevalent nonetheless. This raises questions as to what degree the FCI gains can be attributed to the use of Peer Instruction, to teacher differences, to student ability level or to simply increased familiarity with the question types presented on the FCI.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/109-121-084-717-635, pop00223 tex.number: [object Object]
Keywords: Audio and visual aids; Conceptual learning; Curricula and evaluation; High school; Peer-instruction; Physics; Research in physics education; Teacher training; Teaching methods and strategies; Variations; dept.phy

Charge-coupled device speckle observations of binary stars with the WIYN telescope. v. measures during 2001-2006 - Horch, Elliott P.; van Altena, William F.; Cyr, William M.; Kinsman-Smith, Lori; Srivastava, Amit; Zhou, Jing (The Astronomical Journal, 2008)
A total of 1067 speckle observations of 345 binary stars are presented. Of these, 161 are double stars first resolved by Hipparcos, 17 are resolved for the first time in the observations presented here, and 21 are stars previously discovered by our program and reported in earlier papers in the series. In 947 cases, a magnitude difference is reported along with the relative astrometry. When comparing to systems with very well-known orbits, we find that the root mean square (rms) deviation in separation residuals is 2.81 0.28 mas, and the rms deviation in position angle residuals is 0.88 0.07°. The magnitude difference measures show no significant deviation from Hipparcos photometry, and have average standard deviation of approximately 0.10 mag as judged from repeat observations. Five important systems discovered by Hipparcos are discussed. © 2008. The American Astronomical Society. All rights reserved..
56 citations (Crossref) [2023-10-31] Citation Key Alias: pop00069 tex.type: [object Object]
Keywords: Astrometry; Binaries: visual; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

Sign change of the extended s -wave pairing vertex in the dynamic Hubbard model: A quantum Monte Carlo study - Bouadim, K.; Enjalran, Matthew; Hébert, F.; Batrouni, G. George; Scalettar, Richard T. (Physical Review B, 2008)
The "dynamic" Hubbard Hamiltonian describes interacting fermions on a lattice whose on-site repulsion is modulated by a coupling to a fluctuating bosonic field. We investigate one such model, introduced by Hirsch, using the determinant quantum Monte Carlo method. Our key result is that the extended s -wave pairing vertex, repulsive in the usual static Hubbard model, becomes attractive as the coupling to the fluctuating Bose field increases. The sign problem prevents us from exploring a low enough temperature to see if a superconducting transition occurs. We also observe a stabilization of antiferromagnetic correlations and the Mott gap near half-filling, and a near linear behavior of the energy as a function of particle density which indicates a tendency toward phase separation. © 2008 The American Physical Society.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00117 tex.type: [object Object]
Keywords: dept.phy

Ill-behaved convergence of a model of the Gd3Ga5O12 garnet antiferromagnet with truncated magnetic dipole?dipole interactions - Yavors'kii, T.; Gingras, Michel J. P.; Enjalran, Matthew (Journal of Physics: Condensed Matter, 2007)
Previous studies have found that calculations which consider long-range magnetic dipolar interactions truncated at a finite cut-off distance R c predict spurious (unphysical) long-range ordered phases for Ising and Heisenberg systems on the pyrochlore lattice. In this paper we show that, similar to these two cases, calculations that use truncated dipolar interactions to model the Gd3Ga5O12 garnet antiferromagnet also predict unphysical phases with incommensurate ordering wavevector q ord that is very sensitive to the dipolar cut-off distance R c. © IOP Publishing Ltd.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00283 tex.type: [object Object]
Keywords: Antiferromagnetic materials; Crystal lattices; Finite cut off distance; Gadolinium compounds; Garnets; Heisenberg systems; Magnetic dipolar interactions; Magnetic moments; Numerical methods; Wavevector; dept.phy

A partnership inspiring interest in MSE careers: the center for research on interface structures and phenomena (CRISP) - Caragianis-Broadbridge, Christine; Edgecumbe, Heather; Osenko, Greg; Lehman, Ann; Alter, Lisa; Tully, John C (MRS Proceedings, 2007)
The intent of the CRISP education and outreach effort is to use materials science as a vehicle for enhancing the scientific literacy and knowledge of kindergarten through postgraduate level students. A challenging part of our mission has been inspiring students to take the next step and consider further study (or a career) in the field of Materials Science and Engineering (MSE). The CRISP educational programs were developed through a partnership between Yale University, Southern Connecticut State University and the urban school district of New Haven, CT. An overview of the methods and results of both formal and informal educational program components is included for years one and two of the CRISP MRSEC. This paper will focus on two CRISP programs: 1) MRSEC Initiative for Multidisciplinary Education & Research (MIMER) and 2) "Exploring Materials Science" mobile kits. The evaluation data indicates that the approach used in developing these educational programs is important. Specifically, the impact of these programs is influenced by the students' ability to relate the acquired knowledge to real life applications and technologies. In particular, emphasizing career opportunities rather than just presenting content-based programs is a key element to increasing interest towards further study in Materials Science and Engineering. © 2008 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/131-870-031-945-517 tex.type: [object Object]
Keywords: Career opportunities; Connecticut; Content-based; Educational program; Engineering education; Interface structures; Key elements; Materials; Materials science and engineering; Multidisciplinary education; Post-graduate levels; Professional aspects; Real-life applications; Scientific literacy; Students; Teaching; Urban schools; Yale University; dept.phy

The effectiveness of incorporating conceptual writing assignments into physics instruction - Cummings, Karen; Murphy, Michael (AIP Conference Proceedings, 2007)
This preliminary study examines the impact of conceptual writing assignments on student understanding of two physics concepts. Writing assignments covered the concepts of Newton's Third Law and the impulse-momentum relationship and were given to students in both high school and college level introductory physics classes. The students in these classes along with students in classes taught in an identical fashion by the same instructors without the addition of writing assignments were tested on their conceptual understanding of the two content areas. The results of this initial study indicate that the efficacy of this approach varied with topic. This study further indicates that students' benefit from the writing assignments was independent of their writing ability. © 2007 American Institute of Physics.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/168-392-262-279-442, pop00249 tex.number: [object Object]
Keywords: College; Conceptual learning; High school; Writing; dept.phy

Publishing and refereeing papers in physics education research - Hsu, Leon; Beichner, Robert J; Cummings, Karen; Kolodner, Janet L; Mccullough, Laura (Conference Cognitive Science, 2007)
At the 2007 Physics Education Research Conference, a workshop on publishing and refereeing was held with a panel of editors from four different publishing venues: the physics education research section of the American Journal of Physics, the Journal of the Learning Sciences, Physical Review Special Topics - Physics Education Research, and the Physics Education Research Conference Proceedings. These editors answered questions from participants regarding publishing in their respective venues, as well as writing referee reports that would be useful to both journal editors and authors. This paper summarizes the discussion. © 2007 American Institute of Physics.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Conference proceedings; Journals; Publishing; Referee reports; dept.phy

What factors really influence shifts in students’ attitudes and expectations in an introductory physics course? - Marx, Jeffrey; Cummings, Karen (2006 Physics Education Research Conference, 2007)
To gauge the impact of instruction on students' general expectations about physics and their attitudes about problem solving, we administered two different, but related, survey instruments to students in the first semester of introductory, calculus-based physics at McDaniel College. The surveys we used were the Maryland Physics Expectation Survey (MPEX) and the Attitudes about Problem Solving Survey (APSS). We found that the McDaniel College students' overall responses were more "expert-like" post-instruction: on the MPEX, the students' Overall agree/disagree score started at 59/18 and ended at 63/17, and on the APSS, the students' agreement-score went from 63 to 79. (All scores are out of 100%.) All of the students to whom we administered the MPEX and a significant sub-group to whom we administered the APSS realized these improvements without experiencing any explicit instructional intervention in this course aimed toward improving attitudes and expectations. These results contrast much of the previously reported findings in this area. © 2007 American Institute of Physics.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-519-377-568-644 tex.number: [object Object]
Keywords: dept.phy

Dynamic Hubbard model: a Monte Carlo study - Hébert, F.; Bouadim, K; Enjalran, M; Scalettar, R. T. (AIP Conference Proceedings, 2006)
Dynamic Hubbard models describe relaxation of atomic orbitals when electrons are added to already occupied orbitals, a phenomenon that is not present in the conventional Hubbard model and that may play a role in superconductivity. We use the determinant algorithm to study the properties of a particular dynamic Hubbard model on a two-dimensional square lattice. We report preliminary results for a set of correlation functions, and our data are compared to results from the standard Hubbard model. We find that a dynamic interaction enhances the pair-field susceptibility, signaling the possible on-set of a superconducting phase. © 2006 American Institute of Physics.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-798-190-566-827, pop00239 tex.number: [object Object]
Keywords: Hubbard model; Quantum Monte Carlo; Superconductivity; dept.phy

Comparison of common segmentation techniques applied to transmission electron microscopy images - Sadowski, Thomas; Broadbridge, Christine; Daponte, John S (MRS Proceedings, 2006)
Nanoparticles are of interest in many applications since their decreased size may give them properties that are very different from bulk material. Often nanoparticle properties such as size (diameter) and size distribution are evaluated using transmission electron microscopy (TEM). These parameters, size and size distribution, can be more easily obtained from digitized TEM images by mapping particle signal to black and background pixel to white in a process known as thresholding then performing an algorithm known as a particle analysis. The goal of this study was to compare the ability of several popular thresholding algorithms to segment TEM images. Performance of the thresholding algorithms was evaluated through qualitative and quantitative measures. Results show that the choice of a thresholding algorithm will strongly affect the results obtained from particle analysis. © 2007 Materials Research Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-589-551-901-205 tex.type: [object Object]
Keywords: Algorithms; Bulk material; Image segmentation; Nanoparticles; Parameter estimation; Particle analysis; Size distribution; Thresholding algorithms; Transmission electron microscopy; dept.phy

Computer assisted analysis of microscopy images - Sawicki, M; Munhutu, P; Daponte, John S; Caragianisbroadbridge, Christine; Lehman, Ann; Sadowski, Thomas; Garcia, E; Heyden, C; Mirabelle, L; Benjamin, P (Visualization and Data Analysis, 2009)
The use of Transmission Electron Microscopy (TEM) to characterize the microstructure of a material continues to grow in importance as technological advancements become increasingly more dependent on nanotechnology 1. Since nanoparticle properties such as size (diameter) and size distribution are often important in determining potential applications, a particle analysis is often performed on TEM images. Traditionally done manually, this has the potential to be labor intensive, time consuming, and subjective 2. To resolve these issues, automated particle analysis routines are becoming more widely accepted within the community 3. When using such programs, it is important to compare their performance, in terms of functionality and cost. The primary goal of this study was to apply one such software package, ImageJ to grayscale TEM images of nanoparticles with known size. A secondary goal was to compare this popular open-source general purpose image processing program to two commercial software packages. After a brief investigation of performance and price, ImageJ was identified as the software best suited for the particle analysis conducted in the study. While many ImageJ functions were used, the ability to break agglomerations that occur in specimen preparation into separate particles using a watershed algorithm was particularly helpful 4. © 2009 SPIE-IS&T.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Agglomeration; Commercial softwares; Computer aided analysis; Computer-assisted analysis; Data visualization; Electron microscopes; General purpose; Gray-scale; Image processing; Imaging systems; Labor intensives; Microscopy; Microscopy images; Nanoparticles; Open sources; Particle analysis; Particle size analysis; Potential applications; Semiconductor quantum wires; Software packages; Specimen preparation; TEM images; Technological advancements; Tem; Thresholding; Transmission Electron Microscope (TEM); Transmission electron microscopy; Visualization; Water-shed algorithms; dept.csc; dept.phy

Characterization of nanoparticles by computer imaging particle analysis - DaPonte, J.; Sadowski, T.; Broadbridge, C. C.; Munhutu, P.; Lehman, A.; Krishnamoorthy, D.; Garcia, E. C.; Sawicki, M. S.; Heyden, C.; Mirabelle, L.; Benjamin, P. (Nanomaterials Synthesis, Interfacing, and Integrating in Devices, Circuits, and Systems II, 2007)
Nanoparticles, particles with a diameter of 1-100 nanometers (nm), are of interest in many applications including device fabrication, quantum computing, and sensing because their decreased size may give rise to certain properties that are very different from those exhibited by bulk materials. Further advancement of nanotechnology cannot be realized without an increased understanding of nanoparticle properties such as size (diameter) and size distribution. Frequently, these parameters are evaluated using numerous imaging modalities including transmission electron microscopy (TEM) and atomic force microscopy (AFM). In the past, these parameters have been obtained from digitized images by manually measuring and counting many of these nanoparticles, a task that is highly subjective and labor intensive. Recently, computer imaging particle analysis routines that count and measure objects in a binary image^1 have emerged as an objective and rapid alternative to manual techniques. In this paper a procedure is described that can be used to preprocess a set of gray scale images so that they are correctly thresholded into binary images prior to a particle analysis ultimately resulting in a more accurate assessment of the size and frequency (size distribution) of nanoparticles. Particle analysis was performed on two types of calibration samples imaged using AFM and TEM. Additionally, results of particle analysis can be used for identifying and removing small noise particles from the image. This filtering technique is based on identifying the location of small particles in the binary image, assessing their size, and removing them without affecting the size of other larger particles.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-875-618-829-762, pop00276
Keywords: Atomic force microscopy; Bulk materials; Computer imaging; Device fabrication; Imaging techniques; Nanoparticles; Particle analysis; Quantum computers; Size distribution; Thresholding; Transmission electron microscopy; dept.csc; dept.phy

Application of particle analysis to transmission electron microscopy (TEM) - Daponte, John S; Sadowski, Thomas; Broadbridge, Christine; Day, D; Lehman, A; Krishna, D; Marinella, L; Munhutu, P; Sawicki, M (Visual Information Processing Conference, 2007)
Nanoparticles, particles with a diameter of 1-100 nanometers (nm), are of interest in many applications including device fabrication, quantum computing, and sensing because their size may give them properties that are very different from bulk materials. Further advancement of nanotechnology cannot be obtained without an increased understanding of nanoparticle properties such as size (diameter) and size distribution frequently evaluated using transmission electron microscopy (TEM). In the past, these parameters have been obtained from digitized TEM images by manually measuring and counting many of these nanoparticles, a task that is highly subjective and labor intensive. More recently, computer imaging particle analysis has emerged as an objective alternative by counting and measuring objects in a binary image. This paper will describe the procedures used to preprocess a set of gray scale TEM images so that they could be correctly thresholded into binary images. This allows for a more accurate assessment of the size and frequency (size distribution) of nanoparticles. Several preprocessing methods including pseudo flat field correction and rolling ball background correction were investigated with the rolling ball algorithm yielding the best results. Examples of particle analysis will be presented for different types of materials and different magnifications. In addition, a method based on the results of particle analysis for identifying and removing small noise particles will be discussed. This filtering technique is based on identifying the location of small particles in the binary image and removing them without affecting the size of other larger particles.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Computer imaging; Flat field correction; Flat field correction and rolling ball background correction; Imaging particle analysis; Imaging systems; Magnification; Microfabrication; Nanoparticles; Nanotechnology; Quantum computers; Rolling ball background correction; Size distribution; Transmission electron microscopy; dept.csc; dept.phy

Comparison of thresholding techniques on nanoparticle images - Daponte, John S; Sadowski, Thomas; Broadbridge, Christine; Day, D; Lehman, A; Krishna, D; Marinella, L; Munhutu, P; Sawicki, M (Visual Information Processing Conference, 2007)
Thresholding is an image processing procedure used to convert an image consisting of gray level pixels into a black and white binary image. One application of thresholding is particle analysis. Once foreground objects are separated from the background, a quantitative analysis that characterizes the number, size and shape of particles is obtained which can then be used to evaluate a series of nanoparticle samples. Numerous thresholding techniques exist differing primarily in how they deal with variations in noise, illumination and contrast. In this paper, several popular thresholding algorithms are qualitatively and quantitatively evaluated on transmission electron microscopy (TEM) and atomic force microscopy (AFM) images. Initially, six thresholding algorithms were investigated: Otsu, Riddler-Calvard, Kittler, Entropy, Tsai and Maximum Likelihood. The Riddler-Calvard algorithm was not included in the quantitative analysis because it did not produce acceptable qualitative results for the images in the series. Two quantitative measures were used to evaluate these algorithms. One is based on comparing object area the other on diameter before and after thresholding. For AFM images the Kittler algorithm yielded the best results followed by the Entropy and Maximum Likelihood techniques. The Tsai algorithm yielded the top results for TEM images followed by the Entropy and Kittler methods.
2 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Algorithms; Atomic force microscopy; Binary images; Maximum likelihood; Nanoparticle; Nanoparticle samples; Nanoparticles; Pixels; Riddler-Calvard algorithm; Thresholding; Transmission electron microscopy; Tsai algorithm; dept.csc; dept.phy

Quantitative confirmation of visual improvements to micro-CT bone density images - Daponte, John S; Clark, Michael R; Nelson, Paul; Sadowski, Thomas; Wood, Elizabeth (Visual Information Processing Conference, 2006)
The primary goal of this research was to investigate the ability of quantitative variables to confirm qualitative improvements of the deconvolution algorithm as a preprocessing step in evaluating micro CT bone density images. The analysis of these types of images is important because they are necessary to evaluate various countermeasures used to reduce or potentially reverse bone loss experienced by some astronauts when exposed to extended weightlessness during space travel. Nine low resolution (17.5 microns) CT bone density image sequences, ranging from between 85 to 88 images per sequence, were processed with three preprocessing treatment groups consisting of no preprocessing, preprocessing with a deconvolution algorithm and preprocessing with a Gaussian filter. The quantitative parameters investigated consisted of Bone Volume to Total Volume Ratio, the Structured Model Index, Fractal Dimension, Bone Area Ratio, Bone Thickness Ratio, Euler's Number and the Measure of Enhancement. Trends found in these quantitative variables appear to corroborate the visual improvements observed in the past and suggest which quantitative parameters may be capable of distinguishing between groups that experience bone loss and others that do not.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Algorithms; Bone Thickness Ratio; Computerized tomography; Digital filters; Euler's Number; Gaussian filters; Image enhancement; Image sequences; Medical imaging; Optical resolving power; dept.csc; dept.phy

Animating climate model data - Daponte, John S; Sadowski, Thomas; Thomas, Paul (Visual Information Processing Conference, 2006)
This paper describes a collaborative project conducted by the Computer Science Department at Southern Connecticut State University and NASA's Goddard Institute for Space Science (GISS). Animations of output from a climate simulation math model used at GISS to predict rainfall and circulation have been produced for West Africa from June to September 2002. These early results have assisted scientists at GISS in evaluating the accuracy of the RM3 climate model when compared to similar results obtained from satellite imagery. The results presented below will be refined to better meet the needs of GISS scientists and will be expanded to cover other geographic regions for a variety of time frames.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Animation; Climate model data; Computer simulation; Data reduction; Geographical regions; Imaging systems; Mathematical models; Satellite imagery; Satellites; Simulation math model; dept.csc; dept.phy